Income poverty in Australia Evidence from the HILDA survey - Sila, Urban (OECD Economics Department Working Papers, 2019)
This paper analyses relative income poverty in Australia of individuals aged 15 or more, based on the HILDA Survey data. Australia has above-average poverty rates among OECD countries, but poverty has decreased in the last 15 years. Certain groups are more at risk than others. People living alone and lone parents are at higher risk of poverty. Old people in Australia have a more than 30% chance of living in poverty, which is one of the highest in the OECD. Among those of working age, being employed significantly reduces the risk, while those out of the labour force and the unemployed are at much higher risk of poverty. Nevertheless, there is poverty also among people that work, typically casual workers and part-time workers. People with low education are also at risk. Those living alone and one-parent households face quite a high risk of poverty, even if they are employed. Indigenous Australians are almost twice as likely to be poor than the rest of Australians and they appear significantly poorer than the rest even after controlling for education, age, industry, skill and geographical remoteness, suggesting a range of socio-economic issues, including poor health and discrimination